1995
DOI: 10.1073/pnas.92.26.12260
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E4 allele as a predictor of cholinergic deficits and treatment outcome in Alzheimer disease.

Abstract: Apolipoprotein E (apoE) is critical in the modulation of cholesterol and phospholipid transport between cells of different types. Human apoE is a polymorphic protein with three common alleles, APOc2, APOr3, and APOE4. ApoE4 is associated with sporadic and late-onset familial Alzheimer disease (AD). Gene dose was shown to have an effect on risk of developing AD, age of onset, accumulation of senile plaques in the brain, and reduction of choline acetyltransferase (ChAT) activity in the hippocampus of AD subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
235
1
10

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 549 publications
(262 citation statements)
references
References 43 publications
16
235
1
10
Order By: Relevance
“…15,23,24,26,28 Explanations for these inconsistent findings include aspects of study design, such as small sample size, single versus multiple drug dosing, lack of randomization, variable outcome measures used, variable follow-up periods and variable definitions of response to ChEI treatment; pharmacokinetic and pharmacodynamic characteristics of the different ChEIs used; and genetic heterogeneity in the trial populations. Earlier work had suggested that the greater cholinergic deficit 11 and rate of cognitive decline 12 associated with the carriage of APOE e4 might result in a poorer response to ChEI treatment. However, our finding of an improved response to ChEI treatment with APOE e4 carriage is plausible and consistent with other subsequent treatment studies.…”
Section: Apoe Bche and Chei Treatment Response In Admentioning
confidence: 99%
See 2 more Smart Citations
“…15,23,24,26,28 Explanations for these inconsistent findings include aspects of study design, such as small sample size, single versus multiple drug dosing, lack of randomization, variable outcome measures used, variable follow-up periods and variable definitions of response to ChEI treatment; pharmacokinetic and pharmacodynamic characteristics of the different ChEIs used; and genetic heterogeneity in the trial populations. Earlier work had suggested that the greater cholinergic deficit 11 and rate of cognitive decline 12 associated with the carriage of APOE e4 might result in a poorer response to ChEI treatment. However, our finding of an improved response to ChEI treatment with APOE e4 carriage is plausible and consistent with other subsequent treatment studies.…”
Section: Apoe Bche and Chei Treatment Response In Admentioning
confidence: 99%
“…9 The major genetic risk factor for late-onset (non-familial) AD is carriage of the apolipoprotein E e4 allele (APOE e4). 10 The presence of APOE e4 is associated with a greater cholinergic deficit 11 and rate of cognitive decline 12 than in non-carriers of APOE e4, suggesting a likelihood of poorer clinical response to ChEI treatment. Gender may interact with APOE genotype in cognitive decline and, therefore, may also be a predictor of response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the e4 allele has been shown to promote the neuropathological features of AD, including b-amyloid (Ab) deposition Nagy et al, 1995;Norrman et al, 1995;GomezIsla et al, 1996) and neurofibrillary tangle formation Nagy et al, 1995;Norrman et al, 1995;Gomez-Isla et al, 1996), attempts to relate these features to psychotic symptoms in AD have yielded conflicting results (Zubenko et al, 1991;Förstl et al, 1994;Mukaetova-Ladinska et al, 1995;Sweet et al, 2000). Additionally, ApoE e4 has been linked with more profound cholinergic loss in the frontal cortex (Soininen et al, 1995) and medial temporal lobe (Poirier et al, 1995), and acetylcholine levels have in turn been implicated in psychotic disturbances in AD (Cummings and Kaufer, 1996). Neuroimaging studies may shed additional light on the association between ApoE e4 and psychotic manifestations of AD.…”
Section: Interpretation Of An Increased Risk Of Psychosis In Apoe E4 mentioning
confidence: 99%
“…Among the three major isoforms of ApoE (e2, e3, and e4), the e4 allele has been reported to increase an individual's risk of developing AD, and decrease age of disease onset, in proportion to the number of e4 alleles present (Corder et al, 1993;Farrer et al, 1997). The search for phenotypic correlates of e4 has included neuropathological studies of the rate of b-amyloid (Ab) deposition Nagy et al, 1995;Norrman et al, 1995;Gomez-Isla et al, 1996), neurofibrillary tangle formation Nagy et al, 1995;Norrman et al, 1995;Gomez-Isla et al, 1996), cholinergic markers (Poirier et al, 1995;Soininen et al, 1995), and medial temporal lobe atrophy (Lehtovirta et al, 1996b;Hashimoto et al, 2001;Basso et al, in press).…”
Section: Introductionmentioning
confidence: 99%